Oleanolic Acid Nanofibers Attenuated Particulate Matter-Induced Oxidative Stress in Keratinocytes - Hsuan Fu; Feng-Lin Yen; Pao-Hsien Huang; Chun-Yin Yang; Chia-Hung Yen (MDPI AG, 2021)
Airborne particulate matter (PM) is one of the indicators of air pollution, and it is also the main factor causing oxidative stress in the skin. Oleanolic acid (OA), a natural terpenoid compound, effectively inhibited PM-induced skin aging; however, OA has poor water solubility and skin absorption, which limit its application in medicines and cosmetics. The aim of this study was to prepare oleanolic acid nanofibers (OAnf) and evaluate the effects of OA and OAnf in PM-treated keratinocytes. The results showed that OA dissolved in dissolved in dimethyl sulfoxide (DMSO) attenuated PM-induced reactive oxygen species overproduction, stress-activated protein kinase/Jun-amino-terminal kinase (SAPK/JNK) activation, and the expressions of inflammatory and skin-aging-related proteins. In addition, the nanofiber process of OA effectively improved the water solubility of OA more than 99,000-fold through changing its physicochemical properties, including a surface area increase, particle size reduction, amorphous transformation, and hydrogen bonding formation with excipients. The skin penetration ability of OAnf was consistently over 10-fold higher than that of OA. Moreover, when dissolved in PBS, OAnf displayed superior antioxidant, anti-inflammatory, and anti-skin aging activities in PM-treated keratinocytes than OA. In conclusion, our findings suggest that OAnf could be a topical antioxidant formulation to attenuate skin problems caused by PM.